Extensin arabinosylation is involved in root response to elicitors and limits oomycete colonization. (26th June 2019) - Castilleux, Romain; Plancot, Barbara; Gügi, Bruno; Attard, Agnès; Loutelier-Bourhis, Corinne; Lefranc, Benjamin; Nguema-Ona, Eric; Arkoun, Mustapha; Yvin, Jean-Claude; Driouich, Azeddine; Vicré, Maïté
Abstract: Background and Aims: Extensins are hydroxyproline-rich glycoproteins thought to strengthen the plant cell wall, one of the first barriers against pathogens, through intra- and intermolecular cross-links. The glycan moiety of extensins is believed to confer the correct structural conformation to the glycoprotein, leading to self-assembly within the cell wall that helps limit microbial adherence and invasion. However, this role is not clearly established. Methods: We used Arabidopsis thaliana mutants impaired in extensin arabinosylation to investigate the role of extensin arabinosylation in root–microbe interactions. Mutant and wild-type roots were stimulated to elicit an immune response with flagellin 22 and immunolabelled with a set of anti-extensin antibodies. Roots were also inoculated with a soilborne oomycete, Phytophthora parasitica, to assess the effect of extensin arabinosylation on root colonization. Key Results: A differential distribution of extensin epitopes was observed in wild-type plants in response to elicitation. Elicitation also triggers altered epitope expression in mutant roots compared with wild-type and non-elicited roots. Inoculation with the pathogen P. parasitica resulted in enhanced root colonization for two mutants, specifically xeg113 and rra2 . Conclusions: We provide evidence for a link between extensin arabinosylation and root defence, and propose a model to explain the importance of glycosylation in limiting invasion of root cells by pathogenic oomycetes.